Níveis glicêmicos, alfa-tocoferol, ácido fólico, vitamina b12, homocisteína e índices de consumo de ácidos graxos, em adultos normoglicêmicos e pré diabéticos. - Diniz, Sônia Cristina Pereira de Oliveira Ramalho (2019)
Altered fasting glucose levels and/or impaired glucose tolerance are considered pre-diabetes and risk stages for the development of Type 2 Diabetes Mellitus, being the focus of studies that allow interventions to slow this progression. In this regard, vitamin E plays a critical role as an antioxidant in various pathological conditions, including diabetes and its complications, as well as the consumption of different types of fatty acids. Thus, this thesis aimed to evaluate the relationship between glycemic levels and α-tocopherol, folic acid, vitamin B12 and homocysteine and habitual fat intake in normoglycemic and pre-diabetic adults. This is a cross-sectional study linked to a population-based research involving adults of both sexes in the city of João Pessoa, representative of the East and West Zones. Socioeconomic, demographic and epidemiological data, lifestyle, food consumption, anthropometric and biochemical evaluation were collected. The sample consisted of 233 adults, 41.63% were male and 58.37% female, with a mean fasting blood glucose of 87.7mg / dL (SD = 9.2) and medium α-tocopherol. 21.1µmol / L (SD = 7.4). In the normoglycemic group, fasting blood glucose values were positively associated with serum vitamin E levels (p = 0.007 < 0.05), reflecting that when vitamin E values increased by 1 µmol / L, Fasting blood glucose values increased by an average of 0.39 mg / dL (p = 0.000 < 0.05). In the pre-diabetic group, fasting blood glucose levels were inversely associated with serum α-tocopherol levels, reflecting that when α-tocopherol values increased by 1 µmol / L, fasting blood glucose decreased on average by 0.22mg / dL (p = 0.000 < 0.05). Therefore, based on the results, it was observed the importance of α-tocopherol in the control of fasting glycemia, both for pre-diabetics and normoglycemic patients, in a non-dietary supplement population, contributing to the prevention of hypoglycemia in normoglycemic patients. of hyperglycemia in pre-diabetics. Regarding the second article, which aimed to evaluate the usual consumption of fat, in relation to its quantity and quality, in pre-diabetic and normoglycemic adult individuals, developed using the same sample and variables related to food intake and fasting glucose values. , noting that there were no differences for demographic, socioeconomic, epidemiological and lifestyle variables between the two groups. However, different relationships were observed in each group, between fasting blood glucose values and fat consumption, such as: in the pre-diabetic group, there were inverse relationships with fatty acid tertile consumption (AG) monounsaturated (M) - (15.16 ± 0.65g and 24.11 ± 2.74g) and Index I: S (I: S) - (1.39 ± 0.72g); and positive relationships with the consumption of the w-6: w-3 and w-6: w-9 indices. In the normoglycemic group, there were inverse relationships with the consumption of WM-3 and total fat index W-3 and positive relationship with the consumption of polyunsaturated total fat, w-6: w-3, I: S w indices. -6: w-9. It was concluded that there were no differences between the consumption variables for all fat types between the two groups, but differences were observed when relating these consumption values in each group with the fasting blood glucose values. Based on these results, the needs of different types of fats to prevent blood glucose elevation or reduction are different between normoglycemic and pre-diabetic.